Trichoderma collection from Brazilian soil reveals a new species: T. cerradensis Sp. nov. - Peixoto, Gustavo Henrique Silva; da Silva, Rildo Alexandre Fernandes; Zacaroni, Ana Beatriz; Silva, Thais França; Chaverri, Priscila; Pinho, Danilo Batista; de Mello, Sueli Corrêa Marques (Frontiers in Microbiology, 2025)
Trichoderma spp. are important biological control agents and plant growth promoters. However, only a limited number of species are used in biological control even though the genus contains more than 400 species, with most of them being mycotrophic. In this study, 97 Trichoderma isolates preserved at the EMBRAPA collection (an important source for biocontrol agents) and previously collected from several areas in Brazil were characterized which were identified using various molecular markers (internal transcribed spacers (its), translation elongation factor (tef1α), RNA polymerase II subunit (rpb2), actin (act), and calmodulin (cal). Of these, 54 isolates were found to group in the Harzianum species complex and 32 in Sect. Trichoderma. Others were distributed in the following clades: Strictipilosa complex (one isolate), Longibrachiatum (four isolates), and Brevicompactum (seven isolates). Most of the isolates were identified within 17 known species, whereas Trichoderma inhamatum and T. dorothopsis were synonymized under T. lentiforme and T. koningiopsis, respectively, based on multi-locus phylogenetic analysis and GCPRS criteria. However, two isolates formed a clade apart from previously identified species from Sect. Trichoderma and identified as a new species: T. cerradensis sp. nov. The multigenic characterization of isolates deposited in fungal culture collections is crucial for accurate identification and reveals a diverse range of Trichoderma species in Brazil.